THE APPLICATION OF REMOTE SENSING IN TOURISM AT NUSA DUA TOURIST RESORT OF BALI ISLAND - Darmaputra, Putu Gede Eka; Redi Aryanta, I Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 4 No 1)
The aim of this research is to determine the tourist products and to know whether the visual interpretation of remote sensing and GIS tecnology can be applied in tourism in Nusa Dua Tourist Resort. In the preparation stage, it is necessary to combine data ALOS satellite image with identity ALAV2A044933780 with map, and followed with visual interpretation of satellite image to obtain temporary results concerning tourist products in Nusa Dua tourist resort. The result of satellite visual interpretation was cross checked by insite observations to compare the potentials of coral reef at sea and tourist product on the ground. The combination visual interpretation of satellite image and in site observation of tourist product in Nusa Dua tourist resort enables to obtain spatial mapping for tourism in Nusa Dua tourist resort
Keywords: Visual Interpretation, GIS, coral reef, tourism, tourist product